Enhancing Students' Proficiency in English Grammar Through the Implementation of Snowball Throwing Pedagogical Model - Alfons Napoleon Arsai; Almendita Flora W. Arsai (English Education Department, 2023)
This research endeavors to assess students' proficiency in English grammar pertaining to the past tense through a comparative analysis of their pre-test and post-test scores. Employing the innovative snowball throwing learning model as the intervention strategy, this study aims to augment students' grammatical competence in the past tense. The research methodology adopts a classroom action research approach conducted across two cycles. The subjects comprise Grade X students in the secretary class of the first state Vocational school in Manokwari, selected through purposive sampling from four classes. Research instruments include a reading test, observation sheet, and lesson plan. The initial data analysis of the pre-test yields a result of 29.2, indicating a classification in the poor category. However, following the implementation of the snowball throwing model through two cycles (treatment one and treatment two), noteworthy improvement is observed. Treatment one yields a result of 60.3 in the fair category, while treatment two results in an average score of 80.2, classifying as